LED-activated immobilized Fe-Ce-N tri-doped TiO2 nanocatalyst on glass bed for photocatalytic degradation organic dye from aqueous solutions - Maki, Layegh Khaledi; Maleki, Afshin; Rezaee, Reza; Daraei, Hiva; Yetilmezsoy, Kaan (ELSEVIER, 2019)
The aim of this study was to evaluate the photocatalytic process efficiency of titanium dioxide (TiO2) nanoparticles doped with nitrogen (N), iron (Fe), and cerium (Ce) stabilized on a glass bed for the removal of organic dye from an aqueous medium in the presence of visible light. Synthesis of nanocatalysts was performed by sol-gel method. SEM, XRD, FTIR, DLS, AFM, and Zeta-potential analyses were used to identify and describe the properties of synthesized nanocatalysts. The effect of operating parameters, including pH, initial dye concentration, light intensity, contact time, and nanoparticle type on the removal efficiency was explored in a series of photocatalytic experiments. The results showed that doping TiO2 with N, Fe, and Ce resulted nanoparticles with different sizes and increased the photocatalytic activity as well as the surface charge of TiO2 nanoparticles. The Fe-N-Ce-TiO2 was found as the most efficient nanophotocatalyst among synthesized nanoparticles under both visible light and darkness. The experimental results showed that the removal of dyes in acidic pH was higher than that in neutral and alkaline pH. The complete removal of Direct Blue 15 dye under LED radiation could be achieved in optimal conditions of pH = 5.7, current intensity of 0.68 A (1000 lux), initial concentration of 25 mg/L, nanoparticle dose of 10 mg/cm(2) and 60 min of contact time. Findings of this study clearly demonstrated that the nanocatalytic process of FeCe-N tri-doped TiO2 was highly effective in oxidizing dye pollutants in the visible light range, and the it could be very suitable for areas rich in sunlight for the oxidation of dye contaminants. (C) 2019 Published by Elsevier B.V.
Keywords: Direct Blue 15; Photocatalytic degradation; Doping; LED radiation; Nanocatalyst; TITANIUM-DIOXIDE; WASTE-WATER; BAND-GAP; PHENOL; NANOPARTICLES; PHOTODEGRADATION; MECHANISMS; REDUCTION; OXIDATION; NITROGEN; Biotechnology & Applied Microbiology; Engineering; Environmental Sciences & Ecology